2018
DOI: 10.3390/app8081350
|View full text |Cite
|
Sign up to set email alerts
|

Novel Transient Power Control Schemes for BTB VSCs to Improve Angle Stability

Abstract: This paper proposes two novel power control strategies to improve the angle stability of generators using a Back-to-Back (BTB) system-based voltage source converter (VSC). The proposed power control strategies have two communication systems: a bus angle monitoring system and a special protection system (SPS), respectively. The first power control strategy can emulate the behaviour of the ac transmission to improve the angle stability while supporting the ac voltage at the primary level of the control structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…As mentioned previously, if the converter receives a high P re f vsc order by the TSO, the active power sharply increases with a ramp rate of RRS max , and a large active power is transferred from area 1 to area 2. Based on References [16,17], it was confirmed that converter power control is helpful when the power system has a contingency event; therefore, this control strategy largely contributes to the frequency stability of area 2. However, we can also expect that the angle stability of area 1 could be further worsened.…”
Section: More Detailed Description Of Step Control and Ramp-rate Contmentioning
confidence: 94%
See 2 more Smart Citations
“…As mentioned previously, if the converter receives a high P re f vsc order by the TSO, the active power sharply increases with a ramp rate of RRS max , and a large active power is transferred from area 1 to area 2. Based on References [16,17], it was confirmed that converter power control is helpful when the power system has a contingency event; therefore, this control strategy largely contributes to the frequency stability of area 2. However, we can also expect that the angle stability of area 1 could be further worsened.…”
Section: More Detailed Description Of Step Control and Ramp-rate Contmentioning
confidence: 94%
“…However, the transferred power is not exactly estimated since the output power is varied depending upon contingency event types; thus, it is not suitable for interconnected grids since there is a clear exchange clause in their agreement. In Reference [17], the flexible operation of the generator tripping scheme was achieved without a large decelerating energy as the generators trip, and it was confirmed that a simple converter control strategy that transfers the maximum power reserve instantly to the fault area surely contributes to the stability of the AC network. However, this paper only addressed one kind of step control.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the general classification, the converters used include voltage source inverters (VSIs) and current source inverters (CSIs). VSIs have been introduced in multi-level and multi-phase types, while in recent years, multi-level CSIs have been designed and implemented for harmonic compensation [7]. Likewise, CSIs have undergone their laboratory and industrial evolution and performance reporting and are presented in valid different structures [8].…”
Section: Introductionmentioning
confidence: 99%
“…Different variants of photovoltaic (PV) systems, such as PV concentration [1], maximum power point tracking (MPPT) [2], and/or solar tracking systems, are frequently studied to increase the collection efficiency of PV systems. These systems are divided into two types-passive and active tracking systems.…”
Section: Introductionmentioning
confidence: 99%